The Utilization of 3D Animation as a Learning Medium for the Effectiveness of Students' Learning - Maulidi, Muhammad Rezki; Salim, Agus; Utama, Agus Hadi (Journal of English Language and Education, 2025)
The utilization of 3D animation has emerged as an innovative and promising technology to enhance learning experiences by presenting complex information in an engaging visual format. This study aims to explore the utilization of 3D animation as a learning medium and its impact on students' learning effectiveness. Using the Systematic Literature Review (SLR) method and the PRISMA approach, this research reviews literature from 2019 to 2024. The findings indicate that 3D animation can enhance students' motivation, interest, and learning outcomes. It helps students understand abstract concepts through realistic and interactive visualizations, making learning more engaging and effective. Additionally, this animation allows students to actively participate in the learning process. However, challenges such as hardware limitations and lack of teacher training hinder effective implementation. Therefore, collaboration among technology developers, educators, and policymakers is essential to overcome these barriers and maximize the potential of 3D animation in education. By optimizing the potential of 3D animation, this technology can revolutionize traditional teaching methods by creating more interactive, enjoyable, and relevant learning experiences in the digital era.